Penerapan Model Kooperatif Tipe Teams Games Tournament dalam Meningkatkan Motivasi Belajar Peserta Didik pada Pembelajaran Pendidikan Agama Islam Budi Pekerti - Riski, Rina; Hatikah, Nur; Lubis, Saskia Putri; Arfah, Fitri (Prodi Pendidikan Keagamaan Islam, 2022)
The implementation of the cooperative model of the Teams Games Tournament type is carried out through five main stages, namely the stage of class presentation, learning in group, games, competitions, and awarding to students. The students response to the implementation of Teams Games Tournament was very positive, they felt more motivated and easier to understand the material. The implication of implementing the cooperative model of the Teams Games Tournament type is an increase in students learning motivation in terms of activeness, responsibility, and enthusiasm in participating in lessons. Thus, the cooperative model of the Teams Games Tournament type is an effective alternatif to create more interesting and meaningful PAI-BP learning for students.